Multipurpose cadastre: effectiveness and upgrading of GIS layer management system (GLMS) - Hisam Omar, Abdullah (2007)
DSMM is responsible in providing land related records through the Cadastral Database Management System (CDMS). The system will extract or retrieve cadastral information from the Digital Cadastral Data Base (DCDB) which is the main product of DSMM. In order to comply with the increasing demands from government agencies, private firms and publics, therefore DSMM has took proactive measures in improving the system by introducing GIS Layers Management System (GLMS). With the introduction of GLMS, various layers in GIS ready environment can be provided to the private entities and public usage. GLMS will facilitate the governmentâ€™s vision towards the establishment of modern cadastre in Malaysia. GIS Layer Management System (GLMS) has been introduced under the â€œSPDK Upgradeâ€ project since 2002 by Department of Survey and Mapping Malaysia. GLMS facilitates the creating, capturing and maintaining of spatial data using layers approach. GLMS will become an important system for land development management because of its functionalities and increasing of demands of land-related datasets. Main objective of this research is to study the effectiveness of the GLMS. New layers (GLMS 2) such as building, gazette area, Malay reserved, railway, hydrographic and election region have been created. Analyses shown that GLMS 2 is an effective mechanism towards the development and realization of multipurpose cadastral and e-Cadastre in Malaysia.